PENGARUH ARUS KAS, PROFITABILITAS DAN LEVERAGE TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN INDUSTRI MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Gisela Evi Kristiyani Zalogo (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
Companies experiencing financial distress are negatively correlated with the level of Interest Coverage Ratio. The aim of this research is to find out how cash flow, profitability and leverage impact financial distress in companies listed on the Indonesia Stock Exchange in 2018-2022. A quantitative approach with secondary data was used in data collection. Information about financial performance from the financial reports of food and beverage industry companies on the Indonesia Stock Exchange for 2018–2022 is used. This research looked at 88 companies as a population and 11 companies as a sample. The sampling method used in the research is a purposive sampling technique, namely taking samples with consideration and meeting the specified criteria. The data processing method in this research is to use Multiple Regression Analysis. The results of this research show that Cash Flow (AKO), Profitability (ROA) and Leverage (DAR and DER) do not have a significant effect on Financial Distress. Profitability (ROE) cannot be identified as to its influence on Financial Distress because it experienced an Excluded Variable at the research model analysis stage.